2017
DOI: 10.5194/npg-2017-16
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraining on the Stationarity of Signal with Time-Frequency Surrogates to Enhance the Reliability of Singularity Spectrum Attributes of Random Seismic Noise Wavefield

Abstract: Abstract.Existence of a self-affine long range persistence in the seismic noise time series evidences that the current state of system is not in the pure diffused regime and transition from coherent to incoherent motion is still on progress. Rate of this 15 evolving transition can be indirectly linked to the degree of heterogeneity of medium, thus in this paper we tried to gain an insight into the heterogeneity of the medium by analyzing the width, extreme and asymmetrical trend of multifractal spectrum of sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Coda waves). Pilz and Parolai (2014) showed that the rate of this evolving transition is closely linked to the heterogeneity level of a medium in such a way that for a strong heterogonous medium less time will be needed for falling signal into the diffuse state. Therefore learning the fractality of a seismic noise will indirectly provide the basis for a decision on the potential place for executing this method.…”
mentioning
confidence: 99%
“…Coda waves). Pilz and Parolai (2014) showed that the rate of this evolving transition is closely linked to the heterogeneity level of a medium in such a way that for a strong heterogonous medium less time will be needed for falling signal into the diffuse state. Therefore learning the fractality of a seismic noise will indirectly provide the basis for a decision on the potential place for executing this method.…”
mentioning
confidence: 99%